2013
DOI: 10.5935/0103-507x.20130018
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of constipation in an intensive care unit

Abstract: ObjectivesTo evaluate the incidence of constipation in critical patients on enteral nutrition in a hospital intensive care unit and to correlate this incidence with the variables found for critical patients. MethodsThe present investigation was a retrospective analytical study conducted in the intensive care unit of Hospital Regional da Asa Norte (DF) via the analysis of medical records of patients admitted during the period from January to December 2011. Data on the incidence of constipation and enteral nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 21 publications
2
38
0
8
Order By: Relevance
“…Moreover, Nassar et al (1) stated that constipation is occurred in the majority of their studied patients with no significance in terms of age, sex and admission diagnosis. Similarly, Mostafa et al (14) Spodniewska et al (12) and Guerra et al (15) have reported that the most of their studied patients were constipated. On the other hand, these findings were unsupported by Meinds et al"s (16) findings who found that the constipation occurred commonly in the younger age groups with both sex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Nassar et al (1) stated that constipation is occurred in the majority of their studied patients with no significance in terms of age, sex and admission diagnosis. Similarly, Mostafa et al (14) Spodniewska et al (12) and Guerra et al (15) have reported that the most of their studied patients were constipated. On the other hand, these findings were unsupported by Meinds et al"s (16) findings who found that the constipation occurred commonly in the younger age groups with both sex.…”
Section: Discussionmentioning
confidence: 99%
“…In the same line, Webster, (23) and Fennessy et al (24) concluded that early enteral feeding was beneficial for critically ill patients with low motility. Also, Guerra et al (15) reported a higher constipation rate within patients who had received nutritional support within 72 hours of admission. Webster et al (23) and Bharucha et al (2) stated that constipation was associated with low or lack of dietary fiber intake or due to reduction of gastrointestinal tract motility in critically ill patients.…”
Section: Constipation Occurrence Among Critically Ill Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature the incidence of constipation varies from 16% to 84% in critically ill patients [8][9][10][12][13][14][15]. Main reasons for this variance might be the inhomogeneity of the study populations and the lack of a general definition of regular bowel movement.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of constipation has increased continuously as people change their diet and suffer from psychological and social disturbance, which greatly affects the lives of a large number of office workers and the aged. Constipated people are prone to have intestinal flora disorder and long-term constipation is closely associated with acute cardio-cerebrovascular diseases, dementia and colorectal cancer [1][2][3][4]. Recent studies have shown that constipation treatments have not received adequate research and development over the last ten years as they presented a series of problems in clinical research and application, such as inexact curative effect, weak specificity, multiple side effects and limited therapeutic range [5].…”
Section: Introductionmentioning
confidence: 99%